MENYOAL HADIS PEREMPUAN SEBAGAI FITNAH: ANTARA PEMAHAMAN TEKSTUAL DAN KONTEKSTUAL - Gusnanda; Hanifatul Husna (DIRAYAH : Jurnal Ilmu Hadis, 2025)
This article discusses the misogynist hadith in Islam. The topic is interesting and important to discuss because the understanding of these traditions has an impact on the understanding and stigma of certain people or communities in viewing the social status of women in the public sphere. Mistakes in understanding these traditions often occur due to the use of inappropriate methodologies. For some groups, this hadith is considered as a form of misogynism and cornering women. Such a paradigm is certainly contrary to the basic principles of Islam that safeguard the dignity of women. The author seeks to explore an appropriate methodology to understand the hadith of women as "fitnah". This type of research is text-based qualitative. In the approach, the author uses a descriptive-analytical approach. In analysing the data found, the author uses a set of theories in understanding hadith formulated by hadith scholars. The results of this research conclude that textualist scholars tend to understand the hadith of women as fitnah using the literal meaning. This understanding forms a negative stigma that views women as a source of social problems. On the other hand, contextualist scholars view the hadith as a general warning to human beings not to be lulled by all kinds of pleasures so that they forget Allah SWT. In this context, men also have the potential to be a fitnah for women.